Highest and Best Use Analysis for Landed Houses or Vertical Houses in Kenjeran, Surabaya - Cindy Ellisse Wibisono (Petra Christian University, 2019)
East Surabaya is a territory that is developing in infrastructure and located in a tourism area. With a lot of potential vacant land in East Surabaya, the owner of a vacant land at Bulak Kali Tinjang Timur road, Kenjeran plans to build a residential area.. The decision for the best use of alternative plans, can be obtained using the highest and best use (HBU) analysis method. The HBU analysis itself must fulfill 4 criteria, that is, legally permissible, physically possible, financially profitable, and maximum productivity. The alternative planning obtained is two scenarios of landed houses including conventional and clusters concepts, and also two scenarios of vertical houses icnluding vertical houses with basement and without basement. Of the four scenarios, the HBU is vertical houses without basement’s scenarios, which have an annual IRR of 61%, NPV IDR 329,871,606,870, with payback period 24,63 months and discounted payback period 24,81 months